Pharmacokinetics and tissue distribution of bleomycin-induced idiopathic pulmonary fibrosis rats treated with cryptotanshinone - He, Xiangjun; Zhong, Zhi; Wang, Quan; Jia, Zhenmao; Lu, Jing; Chen, Jianwen; Liu, Peiqing (Frontiers in Pharmacology, 2023)
Cryptotanshinone(CTS), a compound derived from the root of Salvia miltiorrhiza, has been linked to various of diseases, particularly pulmonary fibrosis. In the current study, we investigated the benefit of CTS on Sprague-Dawley (SD) rats induced by bleomycin (BLM) and established high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) methods to compare pharmacokinetics and tissue distribution in subsequent normal and modulated SD rats. The therapeutic effect of CTS on BLM-induced SD rats was evaluated using histopathology, lung function and hydroxyproline content measurement, revealing that CTS significantly improved SD rats induced by BLM. Additionally, a simple, rapid, sensitive and specific HPLC-MS/MS method was developed to determine the pharmacokinetics of various components in rat plasma. Pharmacokinetic studies indicated that CTS was slowly absorbed by oral administration and had low bioavailability and a slow clearance rate. The elimination of pulmonary fibrosis in 28-day rats was slowed down, and the area under the curve was increased compared to the control group. Long-term oral administration of CTS did not accumulate in vivo, but the clearance was slowed down, and the steady-state blood concentration was increased. The tissue distribution study revealed that CTS was widely distributed, with the highest exposure in the lungs and liver. The lung CTS exposure was significantly higher in the model group than in the control group, suggesting that the pathological changes of pulmonary fibrosis were conducive to the lung exposure of CTS and served as the target organ of CTS.